VD_FINDINFO HC / 2010 / 581 vom 26. Oktober 2010 - VD Tribunal cantonal (2010)
ACTION EN MODIFICATION, OBLIGATION D'ENTRETIEN, ENFANT, PRÉVOYANCE PROFESSIONNELLE | 285 al. 1 CC, 286 al. 2 CC, 452 al. 2 CPC, 452 CPC, 37 al. 3 LPP, 37 al. 4 LPP, 37 LPP